2023
DOI: 10.3390/antiox12020371
|View full text |Cite
|
Sign up to set email alerts
|

β Boswellic Acid Blocks Articular Innate Immune Responses: An In Silico and In Vitro Approach to Traditional Medicine

Abstract: Osteoarthritis (OA) is hallmarked as a silent progressive rheumatic disease of the whole joint. The accumulation of inflammatory and catabolic factors such as IL6, TNFα, and COX2 drives the OA pathophysiology into cartilage degradation, synovia inflammation, and bone destruction. There is no clinical available OA treatment. Although traditional ayurvedic medicine has been using Boswellia serrata extracts (BSE) as an antirheumatic treatment for a millennium, none of the BSE components have been clinically appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 112 publications
0
3
0
Order By: Relevance
“…These elements play an important role in the activation liver’s immune response to mitigate the damage and initiate repair processes. , As the enrichment of ficolin 1-rich granules may indicate a specific immune response associated with hepatotoxicity, targeting innate immunity responses has been investigated to control APAP-related toxicity . There are no previous data addressing the ability of the prepared hybrids or their components to directly regulate this marker; still, the ability of boswellic acids to modulate innate immunity in different tissues has been proven. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These elements play an important role in the activation liver’s immune response to mitigate the damage and initiate repair processes. , As the enrichment of ficolin 1-rich granules may indicate a specific immune response associated with hepatotoxicity, targeting innate immunity responses has been investigated to control APAP-related toxicity . There are no previous data addressing the ability of the prepared hybrids or their components to directly regulate this marker; still, the ability of boswellic acids to modulate innate immunity in different tissues has been proven. …”
Section: Resultsmentioning
confidence: 99%
“… 66 There are no previous data addressing the ability of the prepared hybrids or their components to directly regulate this marker; still, the ability of boswellic acids to modulate innate immunity in different tissues has been proven. 67 69 …”
Section: Resultsmentioning
confidence: 99%
“…The TLR4/MyD88/NF-κB signaling pathway has been identified in both human and rat articular chondrocytes [ 25 , 26 ]. Previous chondrocyte experiments [ 27 ] revealed that the activation of the TLR4 signaling pathway in human and animal chondrocytes further activated the downstream NF-κB signaling pathway, and p-NF-κB was the main form of NF-κB activation [ 28 ]. This led to the release of inflammatory factors such as IL-1β, IL-6, and TNF-α.…”
Section: Discussionmentioning
confidence: 99%